Health Literacy and Understanding of Medical Instructions in Multilingual Communities - Nurasia Natsir; Suntin Suntin; Alamsyah Alamsyah (International Journal of Health and Social Behavior, 2026)
Background. Health literacy plays an important role in determining health outcomes; however, in multilingual societies, the interpretation of health information can be influenced by the complexity of language use and communication practices. In South Sulawesi, Indonesia, communities commonly communicate using Indonesian, Bugis, and Makassar languages, yet the impact of linguistic diversity on medical communication remains insufficiently explored. Objective. This study aims to analyze the relationship between language dominance and the ability to comprehend written and oral medical information, while identifying communication challenges experienced in multilingual healthcare settings. Methods. A convergent parallel mixed-methods approach was applied, involving a survey of 320 Community Health Center visitors, 24 in-depth interviews, and discourse analysis of 18 doctor-patient consultations. Quantitative and qualitative findings were integrated through a joint display analysis. Results. The findings revealed that 61.3% of participants demonstrated inadequate health literacy. Bugis-dominant speakers showed significantly lower comprehension scores (M = 52.4) than Indonesian-dominant speakers (M = 71.8; Cohen’s d = 1.84). Frequent code-switching was associated with increased comprehension difficulties (r = 0.47). Linguistic factors contributed an additional 21% to the explained variance, with language dominance identified as the strongest predictor. Qualitative findings revealed four major barriers: unclear biomedical terminology, differences between formal and local language registers, ambiguity in spoken instructions, and limited patient participation. Conclusion. Effective health communication requires greater linguistic adaptation through local-language materials, culturally responsive training for healthcare providers, and assessment approaches that recognize multilingual abilities as strengths rather than limitations.